2017
DOI: 10.1111/1365-2664.12965
|View full text |Cite
|
Sign up to set email alerts
|

Are ranger patrols effective in reducing poaching‐related threats within protected areas?

Abstract: Abstract1. Poaching is one of the greatest threats to wildlife conservation world-wide.However, the spatial and temporal patterns of poaching activities within protected areas, and the effectiveness of ranger patrols and ranger posts in mitigating these threats, are relatively unknown.2. We used 10 years (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) of ranger-based monitoring data and dynamic multi-season occupancy models to quantify poaching-related threats, to examine factors influencing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 50 publications
3
91
0
3
Order By: Relevance
“…Among the few studies for which it was possible to calculate δ , we found 1 instance where it was much higher (Moore et al. ), so we assessed the impact of higher values in the sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the few studies for which it was possible to calculate δ , we found 1 instance where it was much higher (Moore et al. ), so we assessed the impact of higher values in the sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We set appropriate values of effort by estimating δ in a real data set (Hötte et al 2016) and adjusting E in the model to obtain a matching value of δ (0.06) (Supporting Information). Among the few studies for which it was possible to calculate δ, we found 1 instance where it was much higher (Moore et al 2018), so we assessed the impact of higher values in the sensitivity analysis.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this framework is well suited to study spatiotemporal interactions between wildlife and poachers. However, few studies account for the imperfect detection in the occupancy of poachers (Critchlow et al 2015, Moore et al 2018. Such a flexible parameterization can therefore assess the dynamics of species interactions simultaneously with species occupancy and detection (Fidino et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using repeated surveys of detections and non-detections of poaching-related threats, such as snares, and of wildlife collected at several spatial units, one can estimate the temporal variation in the detection and occupancy probabilities of poachers in a given site conditional on the occurrence of wildlife with which they interact. One recent study assessed levels of illegal wildlife killing in a national park in Rwanda by fitting an occupancy model on detection/non-detection of poaching signs directly (Moore et al 2018). However, few studies account for the imperfect detection in the occupancy of poachers (Critchlow et al 2015, Moore et al 2018.…”
Section: Introductionmentioning
confidence: 99%